Penile osteosarcoma - Daniel Abensur Athanazio; Maurício Bessa; José do Egypto Pereira Filho; Paulo Roberto Fontes Athanazio (BMC, 2023)
Abstract Introduction Extraskeletal osteosarcoma arising in the penis is exceedingly rare and its major differential diagnosis is sarcomatoid carcinoma. Case presentation A 19-year-old patient noticed a deep nodule in the dorsal side of the penis 2 years before this presentation. No skin lesions were noted until recent ulceration. In both biopsy and penectomy specimen, atypical mononuclear cells were diffusely positive for SATB2 (a marker of osteoblastic differentiation), CD99 and vimentin. These cells were negative for pan-keratin, SOX10, S100, EMA, GATA3 and CD68 was expressed only in multinucleated giant (osteoclast-like) cells. Few areas suggestive of osteoid production were noted. Conclusion In high-grade sarcomas, including in the penis, SATB2 staining may be useful to identify extraskeletal osteosarcoma.